2021
DOI: 10.1186/s13722-021-00231-z
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and dependence is linked to the extent that people experience need satisfaction while drinking alcohol in two Aboriginal and Torres Strait Islander communities

Abstract: Background Unhealthy alcohol use is a key concern for Aboriginal and Torres Strait Islander (‘Indigenous Australian’) communities. Due to systematic disadvantage and inter-generational trauma, Indigenous Australians may be less likely to have satisfied basic psychological needs (autonomy, competence, and relatedness). When people are need-thwarted, they may engage in compensatory behaviours to feel better in the short-term. We explore the relationship between perceived basic psychological needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
4
0
1
Order By: Relevance
“…It is often unclear who is at risk as some people do not drink out in public—those who feel disconnected from others, or who otherwise have thwarted basic psychological needs might engage in at‐risk drinking to feel better [ 37 ]. Our data suggest that AUDIT‐C and the Finnish method would both be useful tools that communities could use to detect at‐risk drinkers such that they could be supported.…”
Section: Discussionmentioning
confidence: 99%
“…It is often unclear who is at risk as some people do not drink out in public—those who feel disconnected from others, or who otherwise have thwarted basic psychological needs might engage in at‐risk drinking to feel better [ 37 ]. Our data suggest that AUDIT‐C and the Finnish method would both be useful tools that communities could use to detect at‐risk drinkers such that they could be supported.…”
Section: Discussionmentioning
confidence: 99%
“…We found that people who experience need satisfaction while drinking – who feel autonomous, connected to others and competent – are more likely to drink at risky levels, and become dependent. 24 This finding suggests that creating safer ways to meet core psychological needs might be helpful in addressing risky drinking.…”
Section: Using the App For Future Researchmentioning
confidence: 99%
“…Examples of compensatory behaviour in the form of releasing self-control can include alcohol abuse, binge-eating or selfharm. Research among Aboriginal communities indicates that problematic alcohol use is partly rooted in an attempt to meet basic psychological needs [5]. Other studies have clearly shown associations of both frustration and lack of need satisfaction with involvement in alcohol use.…”
Section: Frustration Of Needs Versus Addictionmentioning
confidence: 99%
“…Przykładem zachowań kompensacyjnych w formie zwalniania samokontroli może być nadużywanie alkoholu, napadowe objadanie się czy samookaleczanie. Badania prowadzone wśród społeczności Aborygenów wskazują, że problemowe używanie alkoholu częściowo ma źródła w próbie zaspokojenia podstawowych potrzeb psychologicznych [5]. Inne badania wykazały wyraźnie związki zarówno frustracji, jak i braku zaspokojenia potrzeb z zaangażowaniem w używanie alkoholu.…”
Section: Frustracja Potrzeb a Uzależnienieunclassified
See 1 more Smart Citation